Identity Multiplicity in an Ethnic and Religious Minority in Latvia: Old Believer Youth - Stasulane, Anita (Frontiers in Sociology, 2021)
The paper explores the relationship between the religious identity and the ethnic and national identities of Old Believer youth in Latvia. This case is of particular interest in providing an in-depth insight into the intersection of ethnicity, nationality and religion, as the Old Believers are an ethnic and religious minority living in Latvia. Applying the concepts of multiple identities, this article explores the role of religion played in the integration of identity among young people belonging to the Old Believer religious community: their self-understanding as a composition of intersecting identities that influence each other; the manifestations of the intersection of various identities; the relationship of identity integration to religion. The analysis is based on the findings of ethnographic research conducted in the Old Believer youth group in Daugavpils (Latvia) within a framework of the international project “Cultural Heritage and Identities of Europe’s Future” (CHIEF), funded from the European Union’s Horizon 2020 Research and Innovation Program under Grant Agreement No 770464. The researcher has highlighted that today’s rapid changes are leading to identity crisis: an individual faces difficulty in shaping and maintaining a stable identity, since economic life is becoming increasingly unpredictable and communities are becoming fragmented. The identity of Latvian Old Believer youth forms and develops in a local cultural context, and is affected by the social change. The qualitative data collected during the fieldwork provided a useful resource for an analysis of belonging, the crucial factor in the formation of identity for Old Believer youth. As the voices of young people in this study reveal, three types of belonging characterize Old Believer youth: their ethnicity, which interacts with national belonging in a complex way; the local belonging, which is stronger than the global one; the European belonging, which conflicts with national belonging and ethnicity.